A novel approach to meet the unmet need for family planning - Samanta, Subrata; Dutta, Sujoy; Samanta, Sudipta; Mullick, Agrima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Post-partum intra-uterine contraceptive device is one of the important methods of spacing to meet up the unmet need of family planning. The low complication rate, ease and certainty of insertion and one-time adoption advantages made it an option of family planning by Government of India. In the background of recent trends in family planning, the study aims to establish the efficacy and draw-backs of PP-IUCD among the clients in a tertiary care hospital of West Bengal. Methods: Prospective observational study on 1680 women during January 2016 to December 2016, where the PP-IUCD was given to the patients after vaginal delivery or Cesarean section and were followed up to 3 months. Results: During the study 1.37% patients did not turnup in either follow-up. The most common complication encountered was missing thread (4.64% at 6th week follow-up and 6.67% at 3rd month follow-up). Expulsion rate was much lower (2.02% at 6th week and 2.5% at 3rd month). Heavy bleeding per-vagina was in 1.55% at 6th week and 2.08% at 3rd month. Pain abdomen was .83% at 6th week and 1.67% at 3rd month. Incidence of perforation and failure was both nil at either follow-up. Dysmenorrhea was complained 2.44% at 6th week and 3.33% at 3rd month. Overall satisfaction rate at 6th week (86.05%) was higher than non-satisfaction (13.95%). This was also true for 3rd month where satisfaction rate (77.85%) was higher than non-satisfaction rate (22.15%). Conclusions: PP-IUCD appears to be a safe, efficacious, acceptable and accessible method of contraception.